The Power of Discourse: Reflections on the Obstacles to Social Inclusion of Roma in Serbia - Vidojević, Jelena (Social Inclusion, 2015)
The authors explore the discourses around the exclusion of the Roma in Serbia in two dimensions: social welfare sector and media reports. The paper is structured around the presentation of dimensions contributing to multiple deprivation of Roma in society (from education to labor market participation, social welfare and health care, as well as housing); a review of public policies directed toward the improvement of their position; and analysis of the discourses on Roma within the contexts of the social welfare sector and media reporting. A review of related literature and public policy documents was followed by a qualitative analysis of media reports as well as a review of the secondary sources regarding media discourses on the Roma. This was followed by evidence gathered from semi-structured interviews and discussions with stakeholders in the social welfare sector. The main conclusions of the paper point to the mutual reinforcement of the discourses on the Roma in the social welfare sector and media reports, with their subsequent mutual contribution to social exclusion.